He+ Impact Double Ionization of Noble Gases (Bulletin of Pure and Applied Sciences – Physics, 2020)
Theoretical calculations of He+ impact double ionization of Ne, Ar, Kr and Xe have  been performed in the Modified Binary Encounter Approximation. Direct double  ionization cross sections have been calculated in the modified binary encounter  model. Accurate expression of ∆ (cross section for energy transfer ∆E) and Hatree Fock velocity distributions for the target electrons have been used throughout the  calculations. The present results of double ionization cross sections are in excellent  agreement with the experimental observations in the case of Ne, Ar and Kr  throughout the energy range. The calculated cross sections differs from the  experimental results in the low energy regions in case of Xe because the present  approximation not exhibits better result in the low energy regions, while the over estimations of experimental results in the high energy regions shows that more  theoretical calculations is required to understand the dynamics of the system.